The Impact of Grade Inflation on Higher Education Enrolment and Earnings - Martin Nordin; Gawain Heckley; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2019)
Although grade inflation is unfair and may imply inefficient allocation of human resources, current knowledge of grade inflation effects on individual outcomes is scarce. One explanation is probably the challenge of measuring and estimating causal grade inflation effects. This study examines the consequences of grade inflation at the upper secondary education level on enrolment in higher education and earnings for Sweden. Rigorous diagnostic testing supports our empirical approach. Grade inflation at the school level affects earnings mainly through choice of university and the chosen field of education, rather than through enrolment per se, because attending universities of higher quality and pursuing high-paying fields of education have a substantial impact on earnings. On the other hand, high-skilled students attending upper secondary schools without grade inflation and, unexpectedly, low-skilled women attending "lenient" schools are harmed by this. This causes extensive unfairness and, plausibly, detrimental welfare effects.
Keywords: I20; I21; J24; 330; grade inflation; upper-secondary education; higher education; earnings